2007
DOI: 10.1002/jobm.200700250
|View full text |Cite
|
Sign up to set email alerts
|

Microbial diversity analysis of former salterns in southern Taiwan by 16S rRNA‐based methods

Abstract: The microbiota diversity of the former salterns in southern Taiwan was investigated by denaturing gradient gel electrophoresis (DGGE) and fluorescence in situ hybridization (FISH). Soil samples from three salterns were analyzed using DGGE and 16S rRNA from 502 colonies representing 5 archaea and 18 bacteria taxonomic groups. Each representative taxonomic group was further identified, whereas 8.7% of clones were unclassified microorganisms. Chromohalobacter, Halomonas and Virgibacillus are dominant in the Bieme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…94., 2003 ;7 Yoon et al, 2003 ;8 Yoon et al, 2004 ;9 Romanenko et al, 2005 ;10 Shivaji et al, 2005 ;11 Takai et al, 2005 ;12 Green et al, 2006 ;13 Kim et al, 2006 ;14 Liebgott et al, 2006 ;15 Antunes et al, 2007 ;16 Gu et al, 2007 ;17 Guo et al, 2007 ;18 Yoon et al, 2007 ;19 Xu et al, 2008 ;20 Montes et al, 2008 ;21 Zhang et al, 2008 ;22 Huo et al, 2008 ;23 Roh et al, 2008 ;24 Handley et al, 2009a, 2010 ;25 Wang et al, 2007, 2009 ;26 Aguilera et al, 2009 ;27 Zhuang et al, 2009 and Validation List no. 148., 2012 ;…”
Section: Introductionmentioning
confidence: 99%
“…94., 2003 ;7 Yoon et al, 2003 ;8 Yoon et al, 2004 ;9 Romanenko et al, 2005 ;10 Shivaji et al, 2005 ;11 Takai et al, 2005 ;12 Green et al, 2006 ;13 Kim et al, 2006 ;14 Liebgott et al, 2006 ;15 Antunes et al, 2007 ;16 Gu et al, 2007 ;17 Guo et al, 2007 ;18 Yoon et al, 2007 ;19 Xu et al, 2008 ;20 Montes et al, 2008 ;21 Zhang et al, 2008 ;22 Huo et al, 2008 ;23 Roh et al, 2008 ;24 Handley et al, 2009a, 2010 ;25 Wang et al, 2007, 2009 ;26 Aguilera et al, 2009 ;27 Zhuang et al, 2009 and Validation List no. 148., 2012 ;…”
Section: Introductionmentioning
confidence: 99%
“…Hypersaline environments, although commonly considered "extreme," harbor diverse and active microbial communities [2] and contain organisms that represent all three domains of life [1]. Most microbiological characterizations of hypersaline environments have focused on aquatic communities [1,[3][4][5] and/or microbial mats, such as those found at Guerrero Negro in Mexico, Solar Lake on the Sinai Peninsula in Egypt, and Camargue in France ( [2] and references therein). Far fewer microbiology studies have characterized hypersaline soils [6][7][8][9][10], especially salt mine tunnel soils [11].…”
Section: Introductionmentioning
confidence: 99%
“…Massive sedimentation of halite and other minerals from hypersaline seas occurred during several periods in the Earth's history; an estimated 1.3 million km 3 of salt was deposited in the late Permian and early Triassic periods alone (ca. 240-280 million years ago) [12].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of Haloquadratum, a cosmopolitan halophilic archaeal genus in the crystallizer pans around the world (Maturrano et al, 2006;Baati et al, 2011;Ghai et al, 2011;Dillon et al, 2013) was found to be negligible (<0.3% of available reads) in Siridao salterns. Few studies have also reported the low or negligible occurrence of Haloquadratum in salterns that are very similar in operation with Siridao salterns and other hypersaline environments (Pašić et al, 2005;Wang et al, 2007;Manikandan et al, 2009;Kalwasińska et al, 2018). This may be explained by the lower level of magnesium prevalent in the saltern samples.…”
Section: Halophilic Archaea Tolerate Wide Salinity Fluctuations and Smentioning
confidence: 99%
“…In the intermediate salinity samples (13–18%), bacterial phylotypes affiliated to phyla Proteobacteria , Bacteroidetes , Actinobacteria , and Verrumicrobia were usually encountered while the archaeal members belonged to genera Halorubrum , Haloarcula , and Haloquadratum (phylum Euryarchaeota ). High salinity samples (>25%) were dominated by halophilic archaea belonging to genera such as Haloquadratum and Halorubrum along with a minor contribution from bacterial phylotypes belonging to Bacteroidetes (genus Salinibacter ) ( Mouné et al, 2003 ; Pašić et al, 2005 ; Sørensen et al, 2005 ; Park et al, 2006 ; Wang et al, 2007 ; Baati et al, 2008 , 2010 ; Tsiamis et al, 2008 ; Manikandan et al, 2009 ; Oren et al, 2009 ; Oh et al, 2010 ; López-López et al, 2010 ; Zafrilla et al, 2010 ; Tkavc et al, 2011 ; Trigui et al, 2011 ; Boujelben et al, 2012 ; Dillon et al, 2013 ; Fernandez et al, 2014a , b ; Mani et al, 2015 ; Çinar and Mutlu, 2016 ; Di Meglio et al, 2016 ; Zhang et al, 2016 ; Kalwasińska et al, 2018 ; Leoni et al, 2020 ). In general, archaeal composition from the total prokaryotic community was observed to be between 27–46% at intermediate salinities (13–19%) and 80–90% at high salinities (>25%) ( Ghai et al, 2011 ; Fernandez et al, 2014a , b ).…”
Section: Introductionmentioning
confidence: 99%